1985
DOI: 10.1128/jb.163.1.248-255.1985
|View full text |Cite
|
Sign up to set email alerts
|

TOL plasmid pWW15 contains two nonhomologous, independently regulated catechol 2,3-oxygenase genes

Abstract: Pseudomonas putida MT15 contains a 250-kilobase-pair (kbp) TOL plasmid pWW15, encoding toluene and xylene catabolism, which undergoes large spontaneous deletions to give two classes of mutants with altered catabolic phenotypes (H. Keil and P. A. Williams, J. Gen. Microbiol, 131:1023-1033, 1985). Two structural genes for catechol 2,3-oxygenase (C230) were cloned from pWW15. The gene for C2301 was located on the 2.1-kbp XhoI fragment Xh, whereas that for C2301I was found on the 11.5-kbp BamHI fragment BJ. The tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…1A). The highest similarity (79-81% of identity) was observed with CdoII extradiol dioxygenase of P. putida MT15 (Keil et al, 1985). A subgroup of 11 gene fragments ( Fig.…”
Section: Phylogenetic Affiliation Of Catabolic Genesmentioning
confidence: 88%
“…1A). The highest similarity (79-81% of identity) was observed with CdoII extradiol dioxygenase of P. putida MT15 (Keil et al, 1985). A subgroup of 11 gene fragments ( Fig.…”
Section: Phylogenetic Affiliation Of Catabolic Genesmentioning
confidence: 88%
“…There are several examples of duplications of genes involved in biodegradation of toxic compounds, in particular of genes encoding ring cleavage enzymes. Nonhomologous catechol-2,3-dioxygenase genes have been found in A. eutrophus JMP222 (29,30), in Rhodococcus rhodochrous CTM (44), and in the TOL plasmid pWW15 of P. putida (32). Many naturally occurring TOL plasmids carry duplications of the upper-and/or lower-pathway operons, and/or the xylS and xylR regulatory genes (49); any selective advantage that these duplications might confer upon the plasmid has not yet been defined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the meta-cleavage pathway operon of TOL plasmid pWWO (Harayama et al 1986; Harayama & Rekik 1990) have identified three polypeptides, termed XylXYZ, which together comprise the multi-enzyme complex for the toluate 1,2-dioxygenase. Both TOL plasmids pWWO and pWW53 show a highly conserved restriction pattern within the x y l X Y Z region (Keil et al 1985a) suggesting an identical location of the corresponding catabolic genes on the plasmids (Fig. 1).…”
Section: Resultsmentioning
confidence: 96%
“…putida P a w l . Recombinant plasmids used were pWW53-3403, pWW53-3555, pWW53-3606 (Keil et al 1985a) and pWW53-3825 (Keil et al 1987).…”
Section: Materials and Methods B A C T E R I A L S T R A I N S A N D mentioning
confidence: 99%